ANALISIS HUBUNGAN ANTARA KARAKTERISTIK KELUARGA DALAM MERAWAT KLIEN ISOLASI SOSIAL DENGAN KEMAMPUAN KLIEN BERSOSIALISASI - Komarudin (STIKES Ngesti Waluyo, 2019)
Mental disorder, especially a psychotic (schizophrenia) is chronic condition that the clients have deterioration on their daily activity and social relationship (social isolation). The clients try to keep away from other interaction. This research aim was to identify the relationship between family knowledge and the client socialization ability. The design was a descriptive correlation with cross sectional. The samples were 78 families determined by total sampling. The inclusion criteria were the citizen of Nangkaan sub distric, and accord as a respondent, having mental health disorders family member with social isolation, age between 18 – 60 years, and educational background at least Elementary School. The result shown that mean old age productive age respondent, men, Elementary School, worker, nuclear family, and family relationship as ipar/keponakan. There was a significant relationship between age family, education, and family relationship with the client socialization ability (value p < 0,05). On the hand, family gender, family type, and job were no correlation with the client socialization ability(value p > 0,05). Education and family relationship represent most variable related to with the client socialization ability. Based on the result, it is recommended that the community nurse knowledge about social isolation client and family psychoeducation should be improved.